The Results of Pneumatic Balloon Dilatation Treatment in Children with Achalasia: A Single-Center Experience - Güler, Selen; Aksoy, Betül; Öztan, M. Onur; Appak, Yeliz Ç.; Kahveci Çelik, Sinem; Onbaşı Karabağ, Şenay; Köylüoğlu, Gökhan; Baran, Maşallah (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Achalasia is a primary motility disorder characterized by a relaxation disorder of the lower esophageal sphincter. In pneumatic balloon dilatation, which is one of the treatment methods, the muscle fibers are torn with an endoscopically inflated balloon in the lower esophageal sphincter. This study aimed to evaluate the results of long-term pneumatic balloon dilatation treatment in our clinic for children diagnosed with achalasia. Materials and Methods: Pediatric patients who underwent pneumatic balloon dilatation with a diagnosis of achalasia in our pediatric gastroenterology clinic between 2016 and 2021 were included in the study. Demographic data of the patients, clinical findings at diagnosis, and follow-up results were evaluated retrospectively. Results: Ten patients who underwent 18 pneumatic balloon dilatation operations were included in the study. The mean follow-up period of the patients was 23.7 ± 14.1 months. It was observed that the procedure was performed once in 3 (30%) patients, twice in 2 (20%) patients, and 3 times in 3 (30%) patients. It is noteworthy that the diameter of the balloon used in the first procedure in patients who needed repeated operations was less than 30 mm. No complications were observed except for chest pain, which was detected in 1 patient. Conclusion: When the patients who needed recurrent dilatation were evaluated, it was noted that the diameter of the balloon in which the first procedure was performed in these patients was smaller. This study is an important contribution to the literature due to the scarcity of the pediatric achalasia data, in which long-term results related to pneumatic balloon dilatation are reported in Turkey. Cite this article as: Güler S, Aksoy B, Öztan MO, et al. The results of pneumatic balloon dilatation treatment in children with achalasia: A single-center experience. Turk J Gastroenterol. 2023;34(9):968-974.